2023
DOI: 10.3390/ijms24043685
|View full text |Cite
|
Sign up to set email alerts
|

Urine Metabolomics Exposes Anomalous Recovery after Maximal Exertion in Female ME/CFS Patients

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a debilitating disease with unknown etiology or effective treatments. Post-exertional malaise (PEM) is a key symptom that distinguishes ME/CFS patients. Investigating changes in the urine metabolome between ME/CFS patients and healthy subjects following exertion may help us understand PEM. The aim of this pilot study was to comprehensively characterize the urine metabolomes of eight female healthy sedentary control subjects and ten female ME/CFS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Positive studies: (103,104,384,390) Positive studies: no studies of metabolite levels in blood reported. Multiple reports of brain hypometabolism on imaging (see Table 4).…”
Section: Hypometabolic Statementioning
confidence: 99%
“…Positive studies: (103,104,384,390) Positive studies: no studies of metabolite levels in blood reported. Multiple reports of brain hypometabolism on imaging (see Table 4).…”
Section: Hypometabolic Statementioning
confidence: 99%
“…Previous results showed that the differential metabolites identified here were also associated with CFS in different contexts and animal models, which attests the validity of our work. Among these metabolites, Taurine plays a specifically important role ( Germain et al, 2017 ; Glass et al, 2023 ). Germain et al found that CFS patients had low Taurine content, which was mainly affected by lipid metabolism and amino acids ( Germain et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies on EVs in ME/CFS have been published (Almenar-Pérez et al, 2020;Bonilla et al, 2022;Castro-Marrero et al, 2018;Eguchi et al, 2020;Giloteaux et al, 2023Giloteaux et al, , 2020González-Cebrián et al, 2022;Tsilioni et al, 2022). In 2018, Castro-Marrero and colleagues were the first to analyse EVs isolated from ME/CFS patients and they found a higher EV concentration and smaller sized EVs in 10 ME/CFS patients in comparison to five healthy controls (Castro-Marrero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity and duration of PEM is usually unpredictable, making it challenging for individuals with ME/CFS to plan activities or engage in regular daily tasks (IOM, 2015 ; Stussman et al., 2020 ). Research suggests that PEM may involve dysregulation of the immune system, impaired energy metabolism, and abnormal responses to exertion at the cellular level (Germain et al., 2022 ; Glass et al., 2023 ; Van Booven et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%